Using information to empower nurse managers to become champions for patient safety. - Poniatowski L; Stanley S; Youngberg B (Nursing Administration Quarterly)
There is no longer any question about the risks to patients safety that exist in the hospital. Hospitals are macrosystems that are built upon many interrelated microsystems. Most patient care and hence most errors that directly affect the care outcomes and negatively impact patient safety occur at the microsystem unit level, which is the same level that many improvements to patient safety occur. Patient Safety Net(R) (PSN) is an on-line occurrence reporting tool being used by University HealthSystem Consortium (UHC) member hospitals to report medical events and improve care. As PSN(R) became progressively integrated into the daily operations of these UHC members isolated anecdotes began to surface about how unit nurse managers were able to implement rapid and effective patient safety improvements at the microsystem level on the basis of data received through PSN(R), without involving performance and safety committees mechanisms. This article highlights the survey performed to validate these improvement anecdotes.